Implementation Quality: Lessons Learned in the Context of the Head Start REDI Trial - Domitrovich, Celene E. (2010)
This study uses data collected in the intervention classrooms (N = 22) of Head Start REDI (Research-based, Developmentally Informed), a randomized clinical trial testing the efficacy of a comprehensive preschool curriculum targeting children’s social-emotional competence, language, and emergent literacy skills delivered by teachers who received weekly coaching support. Multiple dimensions of implementation (Dosage, Fidelity, Generalization, and Child Engagement) were assessed across curriculum components. Results indicated that REDI Trainers perceived significant growth in teacher implementation quality over time but that patterns differed by implementation dimension. Dosage and Fidelity of all intervention components were high at the beginning of the year and remained so over time while Generalization was low at baseline but increased significantly across the year. Variation in implementation was associated with variation on several child outcome measures in the social-emotional domain but not in the language and literacy domains.